Do frugivores exert selection on fruiting phenology? : Potential scenarios across three plant populations of a Neotropical vine, Passiflora caerulea - Palacio, Facundo Xavier (2021)
Fruiting phenology is a critical aspect of plant fitness, as it is directly linked to the next-generation offspring delivery. Both abiotic and biotic factors presumably exert natural selection on plant phenology. Despite the role of climate in shaping fruiting phenology is well established, whether frugivores exert phenotypic selection on fruiting phenology has not yet been tested. We estimated the regime and magnitude of frugivore-mediated selection on fruiting phenology in three distant (> 500 km) populations of the Blue Passionflower (Passiflora caerulea) along one year. We measured phenological fruit traits (fruiting onset, fruiting peak, length of the fruiting season) and fruit crop size, and used animal fruit removal as a fitness component. We found highly variable fruiting phenologies between populations, yet phenological stages in lower latitudes were longer than in higher latitudes. One population showed a positive relationship between fruiting onset and fruiting peak among individuals, indicating that fruiting later in the season delayed the fruiting peak. Frugivores favored large fruit crop sizes in the three populations and early fruiting onsets in two populations. In two populations, frugivores selected favorable combinations of fruit crop size and fruiting peak (favoring plants with large crops and early fruiting peaks), as well as favorable combinations of fruiting peak and the length of the fruiting season (favoring plants with early fruiting peaks and extended fruiting seasons). Some degree of similarity in selection patterns among populations suggests that, despite strong geographic variation in climate and animal assemblage composition, some level of functional redundancy occurs in terms of phenotypic trait selection. Overall, our results show that fruiting phenology may be a highly variable life-history trait of plant populations, and support the idea that biotic interactors, conditional on heritable traits and selection pressures sustained over time, could potentially shape phenological fruiting characteristics.